Food Sanitation Hygiene Analysis On Street Vendors In Ujung Batu Sub-District Rokan Hulu In 2021: Analisis Higiene Sanitasi Makanan Pada Pedagang Kaki Lima Di Kelurahan Ujung Batu Kabupaten Rokan Hulu Tahun 2022 - Putri Dafiyanti; Yeyen Gumayesti; Hayana Hayana (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Food sanitation hygiene is an effort to control four factors, namely food, people, places, and equipment that can cause disease or health problems. This study aims to determine the Analysis of Food Sanitation Hygiene on Street Vendors in Ujung Batu Village, Rokan Hulu Regency. The research used is descriptive qualitative with in-depth interviews and observation methods, to 11 informants consisting of 1 head of market management, 5 traders, 5 food consumers. This research was carried out in May 2022 in Ujung Batu Village, Rokan Hulu Regency. The results of this study indicate that traders never check their health, resulting in ignorance of whether food handlers have infectious diseases, traders have dirty nails, do not wear masks, traders do not wash their hands, traders do not use tools such as spoons/forks when taking food/making food. food for consumers. Traders store food in places that are not covered so that vectors can land on food, traders do not use gloves when making food. Trash cans that are not closed cause flies to land on food because the food is also open, traders do not provide hand washing facilities equipped with soap, dirty utensils are not washed immediately, traders do not have a place to store equipment, washed utensils are only placed on the table then covered with a cloth, the water used to wash the equipment was not replaced so the water became oily.